Subsurface iceberg melt key to Greenland fjord freshwater budget. Issue 1 (January 2018) - Moon, T.; Sutherland, D.; Carroll, D.; Felikson, D.; Kehrl, L.; Straneo, F.
Abstract Liquid freshwater fluxes from the Greenland ice sheet affect ocean water properties and circulation on local, regional and basin-wide scales, with associated biosphere effects. The exact impact, however, depends on the volume, timing and location of freshwater releases, which are poorly known. In particular, the transformation of icebergs, which make up roughly 30–50% of the loss of the ice-sheet mass to liquid freshwater, is not well understood. Here we estimate the spatial and temporal distribution of the freshwater flux for the Helheim–Sermilik glacier–fjord system in southeast Greenland using an iceberg-melt model that resolves the subsurface iceberg melt. By estimating seasonal variations in all the freshwater sources, we confirm quantitatively that iceberg melt is the largest annual freshwater source in this system type. We also show that 68–78% of the iceberg melt is released below a depth of 20 m and, seasonally, about 40–100% of that melt is likely to remain at depth, in contrast with the usual model assumptions. Iceberg melt also peaks two months after all the other freshwater sources peak. Our methods provide a framework to assess individual freshwater sources in any tidewater system, and our results are particularly applicable to coastal regions with a high solid-ice discharge in Greenland. Iceberg melt is the largest annual freshwater source in a south Greenland fjord, with release largely below 20 m depth, according to iceberg-model simulations. Furthermore, iceberg melt peaks later in the year than other sources of freshwater.